NILAI PENDIDIKAN ISLAM UNTUK ANAK PADA TEKS HIKAYAT WASIAT NABI MUHAMMAD (Sebuah Kajian Filologi Telaah Isi Teks di Perpustakaan Nasional Jakarta) - Diah Ratna W (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2013)
One of the purposes of this research is to save texts from destruction. Text is checked which is inJakarta National Library. Other texts in the form of mikrofis at Leiden University Library do notfigure out in this research because limitation of opportunity and time. Besides that, this research alsoaimed to state messages which consist in the texts. Considering the condition of the texts which arevery worry than it is needed effort to save them. If the effort to save is not immediately done hence thetext will dossolved in few times later. Destruction texts will not only lost one of national cultural butalso will lost values in that texts. From this texts, it can be obtained clear overview about: thinking,culture, trust, and value of society in the last time. Text A is text which was transliterated. This textbecomes basis through comparison two texts namely text A and B. Text A has more complete episodestory than text B. Values in this saga are messages which want to be submitted by author to readers.Those messages are prohibition and suggestion about jima' and fomentations, help each other andlove humanity, govern sholat for every moslem, glorifying parents and teacher, prohibition doing lapand eat illicit food, which all the things are priority messages. Besides those messages there are alsosubordinate messages for example dzikir, comand to learn and to teach science, sleep procedures,govern taubat, and fomentation start the activity using righ hand.Keyword : Islamic Educational Value